Collaborative Governance pada Pemberantasan Peredaran Narkotika di Kota Tanjungpinang - Sarmadani Sarmadani; Yudhanto Satyagraha Adiputra; Khairi Rahmi (Jurnal Ilmu Komunikasi, Administrasi Publik dan Kebijakan Negara, 2025)
The circulation of narcotics in Tanjungpinang City has increased from 2019 to 2023, despite various programs implemented by relevant agencies. Based on the data, there were 422 suspects apprehended, with 395 suspects acting as distributors (dealers) and 27 suspects as users. The presence of two main institutions, the National Narcotics Agency of Tanjungpinang City and the Narcotics Crime Unit of Tanjungpinang City Police, has not yet been fully effective in reducing the rate of drug trafficking. This study aims to analyze the application of collaborative governance in combating drug trafficking in Tanjungpinang City, based on the theory of Schottle, Haghsheno, and Gehbauer (2014) with seven indicators: willingness to compromise, communication, commitment, mutual trust, transparency/information exchange, knowledge sharing, and willingness to take risks. The method used is a descriptive qualitative approach. Data was collected through interviews and documentation. The research results indicate that willingness to compromise is reflected in cooperation such as joint investigations and coordination in handling suspects. Communication between agencies is conducted both formally and digitally, though not yet structured on a routine basis, it remains responsive. Commitment is demonstrated through Operation Antik, the BNNP prevention program, and the consistent and sustained participation of the DPC GANN. Mutual trust is built through open communication and recognition of each party's role. Transparency and information exchange are evident in the openness of data and access to information between agencies and the public, though technological challenges remain. Knowledge sharing is facilitated through contributions from the National Narcotics Agency (BNN), the police, and former offenders, fostering collective learning. Willingness to take risks is evident in the courage to adopt new approaches for innovation in drug eradication.